Diastereoselective Synthesis of 2-Phenylselenenyl-1,3-anti-Diols and 2-Phenylselenenyl-1,3-anti-Azido-Alcohols via Hydroxyand Azido-Selenenylation Reactions - Renato Noto; Paolo Lo Meo; Michelangelo Gruttadauria; Carmela Aprile; Serena Riela (Molecules, 2005)
A method to synthesize 2-phenylselenenyl-1,3-anti-diols and 2-phenyl- selenenyl-1,3-anti-azidoalcohols via hydroxy- or azido-selenenylation of trans-allylic alcohols is reported. Moreover, the first example of hydroxyl-selenenylation of an allylic azide is presented. Yields ranging from moderate to good and diastereomeric ratios up to 95:5 are achieved.